2016
DOI: 10.1186/s12940-016-0196-y
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric emergency department visits and ambient Air pollution in the U.S. State of Georgia: a case-crossover study

Abstract: BackgroundEstimating the health effects of ambient air pollutant mixtures is necessary to understand the risk of real-life air pollution exposures.MethodsPediatric Emergency Department (ED) visit records for asthma or wheeze (n = 148,256), bronchitis (n = 84,597), pneumonia (n = 90,063), otitis media (n = 422,268) and upper respiratory tract infection (URI) (n = 744,942) were obtained from Georgia hospitals during 2002–2008. Spatially-contiguous daily concentrations of 11 ambient air pollutants were estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 34 publications
5
59
0
6
Order By: Relevance
“…Recent epidemiologic evidence suggests traffic-related air pollution may be a risk factor for respiratory infections and related comorbidities in infants and children 612 . Secondary pollutants including ozone and particulate matter were found to be significantly associated with increased risk for bronchitis, pneumonia, and otitis media in a case crossover study of Georgia pediatric emergency department visits during 2002–2008 13 . Jedrychowski and colleagues reported a dose-response relationship between recurrent bronchiolitis and pneumonia infections and PM 2.5 at the child’s prenatal residence in Krakow, Poland 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiologic evidence suggests traffic-related air pollution may be a risk factor for respiratory infections and related comorbidities in infants and children 612 . Secondary pollutants including ozone and particulate matter were found to be significantly associated with increased risk for bronchitis, pneumonia, and otitis media in a case crossover study of Georgia pediatric emergency department visits during 2002–2008 13 . Jedrychowski and colleagues reported a dose-response relationship between recurrent bronchiolitis and pneumonia infections and PM 2.5 at the child’s prenatal residence in Krakow, Poland 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This increase can be related to levels of ground ozone. As the AQHI is based only on three air pollutants, it also refl ects seasonal changes in their levels [7,8].There are a few publications which used the AQHI as an exposure/risk measure in relation to various health outcomes [9][10][11][12][13][14][15]. We conclude that the estimated higher values on hot days might also have preventive effects on temperature health impacts.…”
mentioning
confidence: 89%
“…It has been shown that air quality indicators such as ozone and particulate matter less than 2.5 μm in diameter (PM 2.5 ) exacerbate upper and lower respiratory infections in early life, increase emergency room visits for respiratory problems and contribute to respiratory-related post-neonatal infant mortality. [6][7][8][9] However, the association between air quality and hospital admissions related to respiratory illness has not been investigated in preterm infants. With regard to socioeconomic status, a study performed in a French regional medical network showed that hospitalisation after very preterm birth was higher for children living in neighbourhoods with a high socioeconomic deprivation index, 10 but it remains unknown if these finding extend to less preterm infants and different health care regions.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…While multiple clinical and demographic risk factors—including gestational age at birth, birthweight, severity of chronic lung disease and presence of pulmonary vascular disease—have been associated with both respiratory morbidity and hospitalisation in preterm infants, data investigating the impact of environmental and sociodemographic influences are relatively sparse. It has been shown that air quality indicators such as ozone and particulate matter less than 2.5 μm in diameter (PM 2.5 ) exacerbate upper and lower respiratory infections in early life, increase emergency room visits for respiratory problems and contribute to respiratory‐related post‐neonatal infant mortality . However, the association between air quality and hospital admissions related to respiratory illness has not been investigated in preterm infants.…”
Section: Introductionmentioning
confidence: 99%